2010
DOI: 10.3109/14767051003678028
|View full text |Cite
|
Sign up to set email alerts
|

Congenital primary hydrothorax: effect of thoracoamniotic shunting on neonatal clinical outcome

Abstract: Congenital hydrothorax although corrected by thoracoamniotic shunting is complicated by severe respiratory distress. The neonatal outcome may be improved limiting degree of prematurity; the presence of thoracoamniotic shunt is not per se an indication of premature birth, at least until GA>35 weeks and adequate pulmonary maturity is reached.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
2
6
0
3
Order By: Relevance
“…Additional factors noted to be associated with survival in the current study included GA at birth and unilateral effusions. This concurs with earlier studies which suggested these factors influence survival in the natural history of fetuses with PEs as well as those that undergo shunting [18,19,21,23]. In fetuses with large macrocystic CCAMs, we found survival significantly associated with a greater GA at birth and higher percent reduction in the size of the lung lesion following shunting.…”
Section: Discussionsupporting
confidence: 93%
“…Additional factors noted to be associated with survival in the current study included GA at birth and unilateral effusions. This concurs with earlier studies which suggested these factors influence survival in the natural history of fetuses with PEs as well as those that undergo shunting [18,19,21,23]. In fetuses with large macrocystic CCAMs, we found survival significantly associated with a greater GA at birth and higher percent reduction in the size of the lung lesion following shunting.…”
Section: Discussionsupporting
confidence: 93%
“…Survival rates have improved significantly in recent years, and Wada et al (21) reported survival rates of 58% and 97.8%, respectively, that can be largely attributed to improved methods of neonatal treatment. Thoracentesis is easy to perform and can reduce distress and improve fetal pulmonary development, but the procedure must be repeated after 24-48 hours in many patients, so thoracoamniotic shunting is usually recommended for fetuses with hydrops (65). Recent studies have indicated that the survival rate for congenital hydrothorax with hydrops is around 60% for patients treated with thoracoamniotic shunting, approximately 50% for those treated with thoracentesis, and from 35% to about 60% for those receiving conservative treatment (4,21).…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…4,56 Entre as diversas condutas descritas, encontrou-se, na literatura, a interrupção da gestação (nos países onde esse procedimento é permitido) 3 , a conduta expectante com acompanhamento ultrassonográfico seriado e a terapia fetal invasiva. 3,5,7,50,56,95 Em 1992, Weber e Philipson 17 realizaram a primeira metanálise que analisou as diversas formas de tratamento. Esses autores observaram que a terapia fetal invasiva apresentava os melhores resultados quando comparada com o acompanhamento ultrassonográfico seriado.…”
Section: -Tratamento Fetalunclassified
“…A partir de então, diversas publicações têm demonstrado que o tratamento fetal melhora o prognóstico em casos selecionados 4,15,56,95 , baseado nos seguintes princípios:…”
Section: -Tratamento Fetalunclassified
See 1 more Smart Citation